2017
DOI: 10.3389/fphar.2017.00321
|View full text |Cite
|
Sign up to set email alerts
|

CD24 Expression Is Increased in 5-Fluorouracil-Treated Esophageal Adenocarcinoma Cells

Abstract: The cancer stem cell (CSC) model suggests that there are subsets of cells within a tumor with increased proliferation and self-renewal capacity, which play a key role in therapeutic resistance. The importance of cyclooxygenase-2 (COX-2) in carcinogenesis has been previously established and the use of COX-2 inhibitors as celecoxib has been shown to exert antitumor effects. The present study investigated whether treatment of esophageal adenocarcinoma (EAC) cells with 5-fluorouracil (5-FU) or the growth of tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Recently, OE19 and OE33 esophageal adenocarcinoma cell subpopulations surviving 5-fluorouracil treatment exhibited an increase in expression of cancer stem cell markers CD24 (600074) and ABCG2. These cells also exerted increased resistance to apoptosis [ 167 ]. Other members of ABC family have been shown related to stemness as well.…”
Section: Search Results and Discussionmentioning
confidence: 99%
“…Recently, OE19 and OE33 esophageal adenocarcinoma cell subpopulations surviving 5-fluorouracil treatment exhibited an increase in expression of cancer stem cell markers CD24 (600074) and ABCG2. These cells also exerted increased resistance to apoptosis [ 167 ]. Other members of ABC family have been shown related to stemness as well.…”
Section: Search Results and Discussionmentioning
confidence: 99%
“…Like other cancers, the identification of esophageal CSCs is based on the specific expression of stemness-related surface markers, including CD24, CD44, CD90, CD133, CLDN4, EpCAM, OV6, and p75NTR, some of which are associated with drug resistance and have the potential to predict the therapeutic response ( Yamaguchi et al, 2016 ; Jiménez et al, 2017 ; Liu et al, 2017 ; Wang et al, 2017 ; Wang D. et al, 2019 ; Sun et al, 2018 ; Xu et al, 2018 ; Lin et al, 2019 ; Figure 1A ). p75NTR, also referred to as CD271, is a receptor of the neurotrophic growth factor family that mediates various cell outcomes, such as cell apoptosis during neurodevelopmental processes ( Barker, 2004 ).…”
Section: Cellular Componentsmentioning
confidence: 99%
“…Previous studies have shown that abnormal overexpression of CD24 is an unfavorable prognostic factor during carcinogenesis in various neoplasms [10,15,23,27,28]. Meanwhile, CD24 can upregulate the activity of STAT3 and the expression of prototype STAT3-regulated genes [29].…”
Section: Discussionmentioning
confidence: 99%
“…Cluster of differentiation (CD) 24 is a small glycosyl phosphatidylinositol (GPI)-linked membrane glycoprotein (27)(28)(29)(30) amino acids in length) with glycosylation sites that bind P-selectin [7,8]. High expression levels of CD24 have been identified in various types of cancers-such as breast, prostate, pancreas, ovary, colorectal, and bladder cancers-and indicate poor prognosis [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%